Customer Value as a Mediator of Service Performance, Brand Image, and Marketing Performance - Irene Yospi; Lauw Sun Hiong; Stivenes Tjin Siam (Journal of Business and Economics Research (JBE), 2026)
This study examines the mediating role of customer value in the relationship between service performance, brand image, and marketing performance within fashion MSMEs. Anchored in value-based marketing logic and signaling theory, this research seeks to explain how internal capabilities and market-based assets are translated into superior performance outcomes. A quantitative approach was employed using Covariance-Based Structural Equation Modeling (CB-SEM) with AMOS, based on data collected from 150 respondents. The findings reveal that service performance has a significant positive effect on customer value, which subsequently enhances marketing performance. However, service performance and brand image do not exert a direct influence on marketing performance. These results indicate that the effectiveness of both operational excellence and symbolic brand attributes is contingent upon their ability to generate customer-perceived value, rather than directly driving performance outcomes. This suggests that customers evaluate offerings through a value lens, integrating functional, emotional, and cost-related considerations before translating them into behavioral responses. Moreover, customer value fully mediates the relationship between service performance and marketing performance, highlighting its role as a critical value-transformation mechanism through which firm-level capabilities are converted into market success. In contrast, the absence of a mediating effect between brand image and marketing performance implies that brand-related signals may lack sufficient strength or credibility in the MSME context, where consumers may prioritize tangible benefits over symbolic associations. This study contributes to the extant literature by reinforcing the centrality of customer value as a bridging construct that links internal resources and external performance, while also challenging the presumed direct effect of brand image in emerging market settings. From a managerial perspective, the findings underscore the importance for MSMEs to move beyond service delivery and brand positioning toward a more holistic, value-oriented strategy focused on delivering superior customer value to achieve sustainable marketing performance.